Ioannis Duns Scoti Notabilia super metaphysicam - Johannes Duns Scotus 1266-1308 (Corpvs Christianorvm. Continuatio mediaeualis, 2017)
John Duns Scotus' "Notabilia super metaphysicam" comprises a series of remarks on Bks. IX and XII of Aristotle's "Metaphysics." The extant evidence points to their originally being either marginal notes on Duns Scotus' own copy of the 'Metaphysics' or scrapbook entries linked to the relevant portions of Aristotle's text by caption letters. It appears that Duns Scotus kept adding to those notes in the course of his career. The 'Notabilia' offers a unique perspective on Duns Scotus' interpretation of Aristotle's 'Metaphysics'. It also contains several original insights on key philosophical issues. This work disappeared from circulation at Duns Scotus' death and was consequently thought to have been lost. Several cross-references to and from other writings by Duns Scotus demonstrate both that the Notabilia here edited for the first time is a genuine work by Duns Scotus and that it is his allegedly lost commentary on the Metaphysics. The current edition is based on the two extant witnesses, 'manuscript M' (Milano, Biblioteca Ambrosiana, C 62 Sup., f. 51ra-98rb), which contains the text in its entirety, and 'manuscript V' (Città del Vaticano, Biblioteca Apostolica Vaticana, Vat. lat. 2182, f. 58vb-60ra), which contains Bks. II-IV in what is probably an older stage of the text